The association between fear of falling and smoothness of lower trunk oscillation in gait varies according to gait speed in community-dwelling older adults. Issue 1 (December 2017) - Asai, Tsuyoshi; Misu, Shogo; Sawa, Ryuichi; Doi, Takehiko; Yamada, Minoru
Abstract Background Fear of falling (FoF) is common in community-dwelling older adults. FoF and increased walking speed are associated with lower trunk oscillation during gait in older adults. We hypothesized that older adults with FoF would struggle to walk safely when instructed to walk faster than usual. Methods Participants included 260 community-dwelling older adults aged over 65 years (mean age = 71.9 ± 3.9 years) who were able to walk independently without an assistive device. Participants were instructed to walk along a 15-m smooth horizontal walkway at self-selected normal and fast gait speeds. During the middle 10 m of the walk, oscillation of the lower trunk and stride times were measured with two accelerometers. We examined associations between gait variables, including harmonic ratio (HR) in vertical, mediolateral (HR-ML) and anteroposterior (HR-AP) directions as indicators of smoothness of lower trunk oscillation, as well as stride time variability (STV) and FoF. Results Gait-speed- and STV- adjusted models showed that FoF was significantly associated with HR-ML in the normal-gait condition (HR-ML: β = - .135, p  = .040), while FoF was significantly associated with HR-AP in the fast-gait condition (HR-AP: β = - .154, p  = .017). Conclusions FoF-related changes in gait vary with gait speed. In older adults with FoF, lower trunk oscillation was less smooth in the lateral direction when they walked at their usual pace. In addition, lower trunk oscillation was also less smooth in the direction of travel when they walked at a faster pace than their usual walking speed.